Measuring irrigation performance in Africa - Svendsen, Mark; Ewing, Mandy; Msangi, Siwa (International Food Policy Research Institute, 2009)
The paper develops indicators to look at the performance of the irrigation sector in Sub-Saharan Africa, where demand for food is high and irrigation has a proven potential to boost levels of agricultural productivity. By looking at six indicator categories—institutional framework, water resource use, irrigation area, irrigation technology, agricultural productivity, and poverty and food security—we assess the potential for improving performance in the agricultural food security sector through increasing irrigation sector investments. The indicators on water resource use indicate ample room for further development of the resource. The share of cultivated area equipped for irrigation in Africa is about a third of the world average and just one-sixth of the value for Asia. The low coverage of irrigation technology and the slow rate of growth in coverage clearly represent a lost opportunity for Africa and a tremendous potential for future investment and policy effort. Finally, African countries produce 38 percent of their crops (by value) from approximately 7 percent of their cultivated land on which water is managed, which again suggests that additional investment in irrigation would pay large benefits. The disproportionate contribution to agricultural production of Africa’s small irrigated area suggests that returns on additional investment in irrigation would be high, both in terms of greater food security for the continent and greater production of export-quality agricultural goods.